Keyakinan Terhadap Malaikat Dalam Sudut Pandang Pendidikan Islam - Riha Datul Aisyah; Amanda Putri Sari; Merli Anggelia; Wismanto Wismanto (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Islamic education is a science that develops the natural potential of humans to become noble human beings who can give to angels. So that all components in education must be in accordance with the goals of Islamic education. The aim of this research is to find out Islamic education which is basically used to form Muslims who are not only knowledgeable but also faithful and devout. This research uses a qualitative method with a library approach, the main source of information is obtained from data originating from the Al-Quran and Sunnah, primary and secondary reference books which discuss the concept of faith, especially metaphysical creeds, and the concept of the goals of Islamic education. The result of this research is to find a relationship and influence between education and faith, so that educational values ​​are found that can be explained from aspects of faith to metaphysics, in this case faith in angels. This aspect provides mental influence and imaginative experiences to students and in this case the concept of values ​​can be applied in the world of Islamic education.